Pengaruh Pemberian Alpukat terhadap Kadar Kolesterol LDL Darah pada Mahasiswa/i Obesitas di Fakultas Kedokteran Universitas HKBP Nommensen Medan - Komandaniel Simanullang; Joseph Partogi Sibarani (Universitas HKBP Nommensen, 2020)
Background: Low Density Lipoprotein (LDL) is a lipoprotein that contains more cholesterol. High levels of blood LDL cholesterol are associated with obesity and increased of risk factor of cardiovascular disease. Avocado (Persea americana) is a well known and popular fruit in society. The active ingredient (omega 9-oleic acid) of avocados can be use to decrease LDL cholesterol levels and increase HDL (High Density Lipoprotein) cholesterol levels in blood in order to reduce the risk factor of cardiovascular disease. Objective: This study aims to determine the effect of avocado consumption on blood LDL cholesterol levels in obese students in Medical Faculty of Universitas HKBP Nommensen. Method: This study used a pre-experimental design one group pretest and posttest study. Subjects were 20 obese students of Medical Faculty of Universitas HKBP Nommensen and selected by simple random sampling technique. For the first 14 days, samples are given dietary intervention and the next 14 days given dietary intervention and avocado juice. Measurement of LDL cholesterol levels was done before and after 14 days given avocado juice. Data analysis used paired T test to analyze differences in blood LDL cholesterol levels before and after being given avocado juice. Results: The results are average value of blood LDL cholesterol levels on pretest was 137.1 mg / dL and posttest was 128.25 mg / dL with mean reduction was 8.85 mg / dL. Paired T test analysis shows that the avocados effect to blood LDL cholesterol is significantly influenced with value of p = 0.036 (p <0.05). Conclusion: There is an effect of avocado consumption on blood LDL cholesterol levels.